Medical neglect and pediatric obesity: Insights from tertiary care obesity treatment programs. Issue 3 (3rd July 2017) - Gray, Jane; Cadieux, Adelle; Sweeney, Brooke; Beck, Amy R.; Edgar, Susan; Eneli, Ihuoma; Getzoff Testa, Elizabeth; Paguio, Kristi; Santos, Melissa; Ward, Wendy L.
ABSTRACT: Interprofessional pediatric obesity treatment teams may consider filing a report for medical neglect with their state child protection agency when a child's family is consistently non-adherent to treatment recommendations and the child is medically at risk. The multifactorial nature of the etiology and treatment of obesity makes this a challenging issue to navigate with families and child protection agencies. The aims of this article are to (a) highlight common challenges faced by teams when addressing medical neglect, and (b) offer insights on navigating the medical protection of children with obesity and associated medical conditions in a way that minimizes adverse outcomes.